Regional hydrogeological prospection for natural mineral water - Saraiva, Giancarlo Pinto [UNESP]; Gastmans, Didier [UNESP]; Santarosa, Lucas Vituri [UNESP] (Lepidus Tecnologia, 2021)
This study proposes a model for hydrogeological assessment and prospection of natural mineral water on a regional scale aimed to select potential areas for implementing natural mineral water projects. The following prospective parameters were used to develop this model: specific capacity; aquifer thickness or geological water reservoir unit; degree of aquifer confinement; potential recharge; well density; economic characterization (size of the consumer market and income); in addition to the characterization and hydrochemical profile, based on the degree of minerali-zation, evaluated based on electrical conductivity, water quality (nitrate) and classification according the mineral potential (fluoride). The information from the selected parameters were evaluated individually through thematic maps and statistically. These parameters were weighted according their importance in the model, that served as the basis for the development of a methodological natural mineral water prospecting model whose result was given through ranking with target areas to be prioritized in a detailed exploratory campaign. In order to validate the model, it was applied in to the area represented by the municipalities with outcrops of rocks from the Guarani Aquifer System (SAG) in the state of São Paulo, resulting in a ranking of potentiality and mineral favorability, pointing out target areas to be prioritized in a detailed research campaign.
Prospecção hidrogeológica regional para águas minerais
Keywords: Guarani Aquifer System; Hydrogeological Prospection; Natural Mineral Water